The Effects of Maria Migrants on the Financial Health of the Residents of Central Florida - Breno Braga; Diana Elliott (Institute of Labor Economics (IZA), 2023)
The influx of climate migrants could challenge many communities in the coming decades. In this study, we estimate the effects of Puerto Rican migration on the financial health of residents in receiving communities after Hurricane Maria. On the one hand, migrants can compete for jobs or crowd out access to governmental safety net programs, contributing to declines in the financial health of residents of the hosting communities. On the other hand, migrants might fill labor market needs and increase the consumption of locally produced goods, helping to stimulate the community's economy. We find little evidence that Puerto Rican migrants negatively impacted the credit health outcomes – such as credit scores and delinquency rates - of residents in receiving communities, even three years after their arrival. On the contrary, existing homeowners in Hispanic communities in Central Florida improved their financial well-being after the arrival of migrants. To help explain this finding, we show suggestive evidence that homeowners might have financially benefited from an increase in their housing value after the arrival of migrants.
Keywords: G51; R23; I31; 330; migration; financial health; housing markets